The Role of the Quality of Perceived Social Support in the Emotion Regulation Strategies of Adolescents in Jakarta [Peran Kualitas Perceived Social Support Terhadap Strategi Regulasi Emosi Remaja di Jakarta] - Edita Kristofora; Agustina Hendriati (ANIMA Indonesian Psychological Journal, 2021)
Adolescents are prone to emotional turmoil. Feedback received from the environment, as a form of support, is required in the process of emotion regulation. Thus, it can be assumed that perceived social support will be associated with emotion regulation. However, research linking both variables has so far included only the relationship between quality social support and a single one of the emotion regulation strategies in late adolescence. This study fills the gap, and aims to examine the relationship between quantity and quality of perceived social support with emotion regulation strategies across the entire adolescent age range in Jakarta. The measuring tool used was the Social Support Questionnaire 6 (quantity of perceived social support and perceived social support satisfaction) and the Emotional Regulation Questionnaire (cognitive reappraisal and expressive suppression strategies). The sample comprised adolescents in Jakarta who had achieved formal educational levels, and who came from families with middle to lower level Status Ekonomi Social (SES; Socio-Economic Status; N = 427). The authors used Pearson Product Correlation and linear regression data analysis techniques. The results showed that thequantity of perceived social support was not significantly associated witheither dimension of emotion regulation. Perceived social support satisfaction was significantly associated with both dimensions of emotional regulation. Teenagers are prone to emotional turmoil. Feedback received from the environment as a form of support is required in the process of emotional regulation. Thus, it can be assumed that perceived social support will be associated to emotion regulation. But researches linking both variables so far only included the relationship of quality social support and one of the emotion regulation strategies in late adolescence. This study fills the gap and aims to examine the relationship between quantity and quality of perceived social support with emotion regulation strategies across the entire adolescence age range in Jakarta. The measuring tool used was Social Support Questionnaire 6 (number of perceived social support and perceived social support satisfaction) and Emotion Regulation Questionnaire (cognitive reappraisal and expressive suppression strategies). The sample was adolescents who have formal education in Jakarta and come from families with middle to lower Status Ekonomi Social (SES; Socio-Economic Status; N = 427). The authors used Pearson Product Correlation and linear regression data analysis techniques. The results showed that the number of perceived social support was not significantly associated with both dimensions of emotion regulation. Perceived social support satisfaction was significantly associated with both dimensions of emotional regulation.